Preparation method of cultural paper and cultural paper prepared thereby

CN122899077APending Publication Date: 2026-10-13KWEICHOW MOUTAI BIOTECHNOLOGY R&D CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610900009.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]目前,该类酒糟多被用作饲料、肥料或直接废弃,在造纸领域中的应用较少,核心问题在于酒糟表面惰性较强,直接添加到植物纤维中易导致与纤维分散不均、结合力薄弱,进而影响纸张的力学性能和使用稳定性

Benefits of technology

纤维素酶特异性作用于酒糟细胞壁的纤维素结晶区,半纤维素酶特异性作用于酒糟细胞壁的半纤维素无定形区,两者协同作用,在不破坏酒糟内部纤维骨架的前提下,定向松解致密的细胞壁结构,在酒糟表面暴露大量活性羟基基团,大幅增加与植物纤维的氢键结合位点。阳离子表面活化在酒糟表面引入带正电的季铵盐官能团,使其能与带负电的植物纤维形成强静电吸附与离子键结合;酶解改性与阳离子表面活化的协同处理有效破坏酒糟内部致密结构,同时在酒糟表面引入活性官能团与阳离子位点;既能显著改善酒糟自身分散性,避免颗粒团聚沉降,又可增强酒糟与植物纤维之间的界面相容性及结合作用力,最终有效提升成品文化用纸的抗张强度等力学性能,同时保证纸张纸面匀度、平滑度及印刷适性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899077A_ABST
    Figure CN122899077A_ABST
Patent Text Reader

Abstract

The present application belongs to papermaking technical field, and relates to a kind of cultural paper preparation method and the cultural paper prepared, and the preparation method includes the following steps: after pretreatment to vinasse, with the complex enzyme of cellulase and hemicellulase according to mass ratio 2-4:1 is carried out enzymolysis modification, then carries out cation surface activation, obtains modified vinasse;Plant fiber paper pulp is mixed with modified vinasse, and functional additive is added, to obtain composite pulp;Composite pulp is sequentially formed by copying, drying, and polishing treatment, to obtain cultural paper.Enzymolysis modification and cation surface activation synergistic treatment effectively destroy the compact structure inside vinasse, while introducing active functional groups and cation sites on the surface of vinasse;It can not only improve the dispersibility of vinasse itself, avoid particle agglomeration and sedimentation, but also enhance the interfacial compatibility and bonding force between vinasse and plant fiber, improve the mechanical properties of cultural paper such as tensile strength, while ensuring the paper surface evenness, smoothness and printing suitability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of papermaking technology, and relates to a method for preparing cultural paper and the resulting cultural paper. Background Technology

[0002] Cultural paper is mainly used in the printing of books, textbooks, periodicals, and office supplies, and has high requirements for paper stiffness, basis weight stability, and printability. Current cultural paper typically uses wood pulp fiber as its main raw material, and its structure relies primarily on hydrogen bonds between fibers. Therefore, methods to improve its performance are relatively limited, often involving increasing fiber content or adding chemical additives. This not only increases production costs but may also lead to environmental burdens.

[0003] During the production of Maotai-flavor liquor, a large amount of by-products such as lees are generated. After long-term high-temperature cooking (usually 90-120℃) and multiple rounds (generally 7-9 rounds) of fermentation, the lees form a dense solid structure with a high degree of cross-linking of cellulose, hemicellulose, and lignin. At the same time, functional components such as polysaccharides, small molecule organic acids, and protein derivatives produced during the fermentation process remain.

[0004] Currently, this type of distiller's grains is mostly used as feed, fertilizer, or directly discarded, and its application in the papermaking industry is relatively limited. The core problem is that the surface of distiller's grains is highly inert, and when directly added to plant fibers, it easily leads to uneven dispersion and weak bonding with the fibers, which in turn affects the mechanical properties and stability of the paper. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing cultural paper and the resulting cultural paper. The method utilizes cellulase specifically acting on the cellulose crystalline region of the cell wall of distiller's grains, and hemicellulase specifically acting on the amorphous hemicellulose region of the cell wall of distiller's grains. The synergistic effect of these two methods, without damaging the internal fibrous skeleton of the distiller's grains, directionally loosens the dense cell wall structure, exposing a large number of active hydroxyl groups on the surface of the distiller's grains, significantly increasing the hydrogen bond sites with plant fibers. Cationic surface activation introduces positively charged quaternary ammonium salt functional groups onto the surface of the distiller's grains, enabling them to form strong electrostatic adsorption and ionic bonds with negatively charged plant fibers. The synergistic treatment of enzymatic modification and cationic surface activation effectively disrupts the dense internal structure of the distiller's grains, while simultaneously introducing active functional groups and cationic sites onto the surface. This significantly improves the dispersibility of the distiller's grains, preventing particle aggregation and sedimentation, and enhances the interfacial compatibility and binding force between the distiller's grains and plant fibers. Ultimately, this effectively improves the tensile strength and other mechanical properties of the finished cultural paper, while ensuring paper surface uniformity, smoothness, and printability.

[0006] In a first aspect, the present invention provides a method for preparing cultural paper, comprising the following steps: Distiller's grains modification: After pretreatment, the distiller's grains are then modified by targeted enzymatic hydrolysis using a compound enzyme, followed by cationic surface activation to obtain modified distiller's grains; wherein, the compound enzyme comprises cellulase and hemicellulase in a mass ratio of 2 to 4:1, the amount of the compound enzyme is 0.8% to 1.5% of the dry weight of the distiller's grains, the pH range of the enzymatic hydrolysis modification is 4.8 to 5.2, the temperature is 50 to 55℃, and the time is 3 to 4 hours; Pulp preparation: Plant fiber pulp is mixed with the modified distiller's grains, and functional additives are added to obtain composite pulp; Papermaking process: The composite pulp is sequentially processed through papermaking, drying, and calendering to obtain cultural paper.

[0007] In some embodiments, the enzymatic modification is carried out in a 10%–15% mass concentration of distiller's grains slurry; after the enzymatic modification is completed, the enzymatic product is heated to 90–95°C for 15–20 min to inactivate it, centrifuged or washed and dried, and then the cationic surface activation is carried out.

[0008] In some embodiments, the cationic surface activation is performed using a cationizing agent, which includes at least one selected from 3-chloro-2-hydroxypropyltrimethylammonium chloride, glycidyltrimethylammonium chloride, glycidyltrimethylammonium bromide, and 3-chloro-2-hydroxypropyltrimethylammonium bromide; the cationic surface activation temperature is 60°C to 65°C, and the time is 2 hours to 3 hours. Preferably, the mass fraction of the cationizing agent is 2% to 3% (based on the total mass of the aqueous solution), and the solid-liquid ratio of the cationizing agent to the lees is 1:(10 to 15), wherein the solid-liquid ratio is the ratio of the dry mass of the lees to the mass of the cationizing agent aqueous solution.

[0009] In some implementations, the method for pretreating the distiller's grains includes: Drying and pulverizing: The lees are dried to a moisture content of ≤8%, and then pulverized and sieved in sequence to obtain lees particles that can pass through a 200-mesh standard sieve; Degreasing and impurity removal: The lees particles are soaked in an alcohol solution, then washed and dried. The soaking temperature of the alcohol solution is 60~70℃, the soaking time of the alcohol solution is 2~3h, and the solid-liquid ratio of the lees particles to the aqueous alcohol solution is 1:(8~12). Preferably, the alcohol solution includes at least one of ethanol solution, isopropanol, and methanol; Preferably, the volume concentration of the alcohol solution is 70% to 80%.

[0010] In some embodiments, the plant fiber pulp in the pulp preparation step comprises bleached softwood pulp and hardwood pulp, wherein the weight ratio of softwood pulp to hardwood pulp is 1:(0.5~2).

[0011] In some embodiments, in the pulp preparation step, the weight ratio of the plant fiber pulp to the modified distiller's grains and the functional additives is (70~95):(2~25):(3~8).

[0012] In some embodiments, the functional additives include retention aids, sizing agents, and reinforcing agents; the mass ratio of the retention aid, sizing agent, and reinforcing agent is (0.5~2):(1~3):(1~3). Preferably, the retention aid includes at least one of cationic starch and polyacrylamide, the sizing agent includes at least one of alkyl ketene dimer and neutral sizing agent CS-200, and the reinforcing agent includes one of sodium carboxymethyl cellulose and guar gum.

[0013] In some embodiments, the drying method in the paper forming step is a three-stage drying, which includes a first stage drying, a second stage drying, and a third stage drying. The temperature of the first stage drying is 80~90℃ and the time is 20~30s. The temperature of the second stage drying is 110~120℃ and the time is 15~20s. The temperature of the third stage drying is 90~100℃ and the time is 10~15s.

[0014] In some embodiments, during the paper forming step, the calendering treatment is carried out at a temperature of 60-70°C, a pressure of 0.2-0.3 MPa, and a linear speed of 30-40 m / min.

[0015] Secondly, the present invention provides a cultural paper prepared by any of the above-mentioned methods, wherein the cultural paper uses the plant fiber as the matrix and the modified distiller's grains as the reinforcing component, and forms chemical connections through hydrogen bonding, electrostatic adsorption and ionic bonding, while forming physical interweaving through micro-nano pore embedding and network skeleton filling, thus constituting a chemically bonded-physically interwoven composite structure.

[0016] In summary, this application includes at least one of the following beneficial technical effects: Cellulase specifically targets the cellulose crystalline region of the cell wall in distiller's grains, while hemicellulase specifically targets the amorphous region of hemicellulose in the cell wall. Their synergistic action, without damaging the internal fibrous skeleton of the distiller's grains, directionally loosens the dense cell wall structure, exposing a large number of active hydroxyl groups on the surface of the distiller's grains and significantly increasing hydrogen bond sites with plant fibers. Cationic surface activation introduces positively charged quaternary ammonium salt functional groups onto the surface of the distiller's grains, enabling them to form strong electrostatic adsorption and ionic bonds with negatively charged plant fibers. The synergistic treatment of enzymatic modification and cationic surface activation effectively disrupts the dense internal structure of the distiller's grains while introducing active functional groups and cationic sites onto the surface. This significantly improves the dispersibility of the distiller's grains, preventing particle aggregation and sedimentation, and enhances the interfacial compatibility and binding force between the distiller's grains and plant fibers. Ultimately, this effectively improves the tensile strength and other mechanical properties of the finished cultural paper, while ensuring paper surface uniformity, smoothness, and printability. Attached Figure Description

[0017] Figure 1 The Fourier transform infrared (FT-IR) spectrum of the modified distiller's grains in Example 1 of this application is shown below. Figure 2 This is a scanning electron microscope (SEM) image of cultural paper from Embodiment 1 of this application. Detailed Implementation

[0018] The following specific embodiments further illustrate the technical solution of the present invention. These specific embodiments do not represent a limitation on the scope of protection of the present invention. Non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the scope of protection of the present invention.

[0019] As described in the background section, distillers' grains, due to their strong surface inertness, are currently rarely used in the papermaking industry because their direct addition to plant fibers can easily lead to uneven dispersion and weak bonding, which in turn affects the mechanical properties and stability of the paper.

[0020] To solve the above-mentioned technical problems, this application provides a method for preparing cultural paper and the resulting cultural paper.

[0021] The dry basis of distiller's grains mentioned in this application refers to the absolute dry solid mass obtained by drying the distiller's grains to be treated in an atmospheric pressure oven at 105℃±2℃ until constant weight, and then deducting all moisture.

[0022] Unless otherwise specified, all reagents and materials used in this application are commercially available.

[0023] This application provides a method for preparing cultural paper, comprising the following steps: Distiller's grains modification: After pretreatment, the distiller's grains are then modified by targeted enzymatic hydrolysis using a compound enzyme, followed by cationic surface activation to obtain modified distiller's grains; wherein, the compound enzyme comprises cellulase and hemicellulase in a mass ratio of 2 to 4:1, the amount of the compound enzyme is 0.8% to 1.5% of the dry weight of the distiller's grains, the pH range of the enzymatic hydrolysis modification is 4.8 to 5.2, the temperature is 50 to 55℃, and the time is 3 to 4 hours; Pulp preparation: Plant fiber pulp is mixed with the modified distiller's grains, and functional additives are added to obtain composite pulp; Papermaking process: The composite pulp is sequentially processed through papermaking, drying, and calendering to obtain cultural paper.

[0024] By pretreating the distiller's grains, cellulase specifically acts on the cellulose crystalline region of the cell wall, hydrolyzing β-1,4 glycosidic bonds, cleaving long-chain cellulose molecules, and breaking the rigid skeletal structure of the cell wall; hemicellulase specifically acts on the amorphous region of hemicellulose in the cell wall, hydrolyzing the glycosidic bonds between hemicellulose molecules, and loosening the cross-linking network between cellulose and lignin. The synergistic effect of the two can directionally loosen the dense cell wall structure without damaging the internal fiber skeleton of the distiller's grains, exposing a large number of active hydroxyl groups on the surface of the distiller's grains, and significantly increasing the hydrogen bond binding sites with plant fibers. Cationic surface activation can introduce positively charged quaternary ammonium salt functional groups on the surface of distiller's grains, enabling them to form strong electrostatic adsorption and ionic bonds with negatively charged plant fibers. The synergistic treatment of enzymatic modification and cationic surface activation can effectively destroy the dense internal structure of distiller's grains, while introducing active functional groups and cationic sites on the surface of distiller's grains. This can significantly improve the dispersibility of distiller's grains, prevent particle agglomeration and sedimentation, and enhance the interfacial compatibility and binding force between distiller's grains and plant fibers. Ultimately, this can effectively improve the tensile strength and other mechanical properties of the finished cultural paper, while ensuring the paper surface uniformity, smoothness and printability.

[0025] The dosage of the compound enzyme should be controlled at 0.8% to 1.5% of the dry weight of the distiller's grains. For example, the dosage can be 0.8%, 1.0%, 1.2%, 1.5%, or a combination of both of these. This ensures sufficient enzyme quantity without over-promoting the distiller's grains, achieving adequate surface modification while avoiding excessive cellulose degradation due to excessive enzyme. If the compound enzyme dosage is less than 0.8% of the dry weight of the distiller's grains, the enzyme quantity is insufficient, resulting in inadequate surface modification, low exposure of active hydroxyl groups, weak binding force with fibers, and minimal improvement in paper strength. If the compound enzyme dosage is greater than 1.5% of the dry weight of the distiller's grains, the enzyme is excessive, leading to excessive degradation of distiller's grains cellulose, resulting in broken distiller's grains fiber skeleton, decreased paper strength, and increased dust shedding.

[0026] Controlling the pH range for enzymatic hydrolysis modification to 4.8–5.2, such as 4.8, 4.9, 5.0, 5.1, 5.2, or a combination of both, allows both cellulase and hemicellulase to maintain peak catalytic activity, ensuring efficient and stable enzymatic hydrolysis. At pH < 4.8, enzyme activity significantly decreases, catalytic efficiency drops drastically, and modification is insufficient within the same timeframe; at pH > 5.2, enzyme proteins denature and become inactive, preventing effective enzymatic hydrolysis and resulting in modification failure.

[0027] The enzymatic hydrolysis modification temperature should be controlled at 50-55℃, and the time at 3-4 hours. For example, the temperature can be within a range of 50℃, 51℃, 52℃, 53℃, 54℃, 55℃, or a combination of two of these ranges, and the time can be within a range of 3 hours, 3.2 hours, 3.5 hours, 3.8 hours, 4 hours, or a combination of two of these ranges. This ensures that the enzymatic hydrolysis reaction proceeds fully while maintaining enzyme activity. If the temperature is below 50℃, the enzymatic hydrolysis rate is too slow, and the expected modification effect cannot be achieved within 3-4 hours. If the temperature is above 55℃, the enzyme is rapidly inactivated, the reaction terminates prematurely, and the modification is insufficient. If the time is less than 3 hours, the reaction time is insufficient, the enzymatic hydrolysis is incomplete, and the structure of the distiller's grains is not effectively loosened. If the time is greater than 4 hours, the reaction is excessive, and the distiller's grains fibers are excessively degraded, resulting in structural damage.

[0028] The mass ratio of cellulase to hemicellulase should be controlled at 2-4:1, for example, 2:1, 3:1, or 4:1. This allows the two enzymes to work synergistically, targeting and degrading the cellulose crystalline region and the hemicellulose amorphous region of the cell wall of distiller's grains, respectively, achieving precise and directional loosening of the dense structure of the distiller's grains. A cellulase:hemicellulase ratio < 2:1 indicates insufficient cellulase, which cannot effectively degrade the crystalline region of the cell wall, making it difficult to open the dense structure of the distiller's grains and limiting the improvement in binding force. A cellulase:hemicellulase ratio > 4:1 indicates insufficient hemicellulase, resulting in incomplete degradation of the amorphous region and localized over-degradation, leading to uneven distiller's grains structure and affecting paper uniformity.

[0029] Furthermore, the enzymatic modification is carried out in a 10%–15% mass concentration of distiller's grains slurry; after the enzymatic modification is completed, the enzymatic product is heated to 90–95°C for 15–20 min to inactivate it, centrifuged or washed and dried, and then the cationic surface activation is carried out.

[0030] The optimal mass transfer concentration for enzymatic hydrolysis modification is controlled at 10%–15% of the distillers' grains slurry concentration. For example, the slurry concentration can be within the range of 10%, 11%, 12%, 13%, 14%, 15%, or any two of these values. This avoids the problems of low enzyme activity, excessively large reaction system volume, and high energy consumption caused by excessively low slurry concentration, while also solving the defects of high slurry viscosity, insufficient contact between enzyme molecules and fibers, and uneven enzymatic hydrolysis caused by excessively high concentration. Below 10%, enzyme molecules are over-diluted, reducing the number of effective collisions between enzyme and fiber per unit volume and decreasing enzymatic hydrolysis efficiency. Above 15%, the slurry viscosity increases sharply, resulting in localized over-hydrolysis and localized unreacted stratification. At high concentrations, mass transfer is hindered, and enzyme molecules cannot penetrate into the fiber interior, only undergoing surface hydrolysis, which prevents the opening of the fiber's internal pores.

[0031] Inactivation at 90–95℃ for 15–20 minutes (e.g., inactivation temperatures of 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, or any two of these ranges) and inactivation times of 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, or any two of these ranges) can completely inactivate the complex enzyme, precisely terminating the enzymatic reaction and preventing excessive enzymatic hydrolysis that could lead to fiber skeleton collapse and a decrease in specific surface area. Simultaneously, this temperature is far below the thermal degradation temperature of distillers' grains fiber, thus not damaging the fiber's microstructure or producing byproducts such as caramelization or carbonization. Inactivation below 90℃ or for less than 15 minutes cannot achieve complete inactivation of the complex enzyme; residual enzyme activity will continue to slowly degrade the fiber during subsequent storage, centrifugation, and cationic activation, leading to fiber skeleton collapse and pore closure. While inactivation can be complete at temperatures above 95℃ or for more than 20 minutes, it can cause dehydration condensation reactions of the active hydroxyl groups on the fiber surface, reducing effective grafting sites.

[0032] Furthermore, the cationic surface activation is performed using a cationizing agent, which includes at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, glycidyltrimethylammonium chloride, glycidyltrimethylammonium bromide, and 3-chloro-2-hydroxypropyltrimethylammonium bromide.

[0033] Cationic surface activation with cationic reagents can introduce positively charged cationic functional groups onto the surface of distiller's grains through covalent grafting reactions, thereby altering the surface charge properties. Non-cationic reagents, on the other hand, cannot introduce positive charges onto the surface of distiller's grains and cannot form electrostatic adsorption with negatively charged plant fibers, resulting in poor adhesion between the grains and fibers and easy detachment and powdering. Among these, the epoxy active groups of 3-chloro-2-hydroxypropyltrimethylammonium chloride can undergo ring-opening reactions with the exposed hydroxyl groups on the surface of distiller's grains, stably grafting quaternary ammonium salt groups onto the surface, thus giving the entire distiller's grains a positive charge.

[0034] Furthermore, the temperature for cation surface activation is 60℃~65℃, and the time is 2h~3h.

[0035] Controlling the cation surface activation temperature to 60℃~65℃ and the time to 2h~3h, for example, the temperature can be 60℃, 61℃, 62℃, 63℃, 64℃, 65℃ or a combination of both, and the time can be 2h, 2.2h, 2.5h, 2.7h, 3h or a combination of both, ensures the grafting reaction proceeds fully while avoiding reagent decomposition and side reactions. If the temperature is <60℃, the activation energy is insufficient, the grafting rate is slow, and the expected grafting effect cannot be achieved within 2-3h. If the temperature is >65℃, 3-chloro-2-hydroxypropyltrimethylammonium chloride undergoes thermal decomposition, losing its reactivity, and side reactions increase, affecting the modification effect. If the time is <2h, the reaction time is insufficient, the grafting reaction is incomplete, and the amount of cation groups inoculated is small. If the time is >3h, the reaction is excessive, increasing by-products and leading to over-modification of the distiller's grains surface, affecting its bonding with fibers.

[0036] Furthermore, the mass concentration of the cationizing agent is 2% to 3%, and the solid-liquid ratio of the cationizing agent to the distiller's grains is 1:(10 to 15).

[0037] The mass fraction of the cationizing reagent is controlled at 2% to 3%, and the solid-liquid ratio is 1:(10 to 15). For example, the mass concentration can be 2%, 2.3%, 2.5%, 2.7%, 2.8%, 3%, or a combination of both. Similarly, the solid-liquid ratio of the cationizing reagent to the lees can be 1:10, 1:12, 1:13, 1:15, or a combination of both. This ensures sufficient contact between the reagent and the lees, providing adequate active groups and improving the grafting rate. If the cation reagent concentration is <2%, there are insufficient active groups, resulting in a low grafting rate, insufficient positive charge density on the lees surface, and weak electrostatic adsorption. If the cation reagent concentration is >3%, there is excess reagent, and unreacted reagent remains in the system, affecting the pulp charge balance and reducing the retention aid effect. If the solid-liquid ratio is <1:10, the system concentration is too high, resulting in uneven reagent dispersion and insufficient contact between some lees and the reagent, leading to uneven activation. If the solid-liquid ratio is >1:15, the system concentration is too low, reducing the probability of reagent molecule collisions, slowing the grafting reaction rate, and resulting in insufficient grafting rate within the same time frame.

[0038] Further methods for pretreatment of distiller's grains include: Drying and pulverizing: The lees are dried to a moisture content of ≤8%, and then pulverized and sieved in sequence to obtain lees particles that can pass through a 200-mesh standard sieve; Degreasing and impurity removal: The lees particles are soaked in an alcohol solution, then washed and dried. The soaking temperature of the alcohol solution is 60~70℃, the soaking time is 2~3h, and the solid-liquid ratio of the lees particles to the alcohol solution is 1:(8~12).

[0039] Control the drying of the lees to a moisture content ≤8%, for example, a moisture content of 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or a combination of both. This removes excess free water from the lees, preventing clumping due to excessive viscosity during grinding and avoiding over-diluting of the subsequent enzymatic hydrolysis system, thus maintaining stable enzyme concentration. If the moisture content is >8%, the lees become significantly more viscous, easily forming large clumps during grinding, making it impossible to obtain particles with uniform size; simultaneously, excess water dilutes the subsequent enzymatic hydrolysis system, leading to incomplete enzymatic hydrolysis.

[0040] Controlling the particle size of distiller's grains to allow them to pass through a 200-mesh standard sieve increases the specific surface area of ​​the distiller's grains, enabling subsequent enzymatic hydrolysis and cationization reagents to fully contact the grains and achieve uniform and efficient modification reactions. If the particle size cannot pass through the 200-mesh standard sieve, the specific surface area of ​​the distiller's grains is insufficient, and enzymatic hydrolysis and cationic surface activation can only occur on the surface of the particles, preventing effective modification of the internal structure and reducing the binding force with plant fibers.

[0041] Alcoholic solution soaking for defatting and impurity removal selectively dissolves and removes lipids, waxes, natural pigments, and soluble small molecule impurities from the surface and intercellular spaces of the lees. This breaks down the barrier of lipids and waxes encapsulating the cell walls of the lees, allowing cellulase, hemicellulase, and cationic reagents to penetrate smoothly into the lees. It also eliminates the interference of soluble small molecule impurities on inter-fiber hydrogen bonding and electrostatic adsorption between lees and fibers, further enhancing interfacial bonding.

[0042] The optimal soaking temperature for the alcohol solution is 60-70℃, the soaking time is 2-3 hours, and the solid-liquid ratio of the lees particles to the alcohol solution is 1:(8-12). For example, the temperature can be 60℃, 62℃, 65℃, 65℃, 68℃, 70℃, or a combination of both; the soaking time can be 2 hours, 2.2 hours, 2.5 hours, 2.7 hours, 3 hours, or a combination of both; and the solid-liquid ratio can be 1:8, 1:9, 1:10, 1:11, 1:12, or a combination of both. This method effectively removes oil and impurities. If the soaking temperature is below 60℃, the lipid dissolution rate is slow, and effective degreasing cannot be completed within 2-3 hours, resulting in high levels of residual impurities. If the soaking temperature is above 70℃, ethanol evaporates rapidly, the solvent concentration drops sharply, and the degreasing effect deteriorates. If the soaking time is less than 2 hours, impurities are not fully removed, and residual small molecules can interfere with subsequent reactions, increasing the risk of paper dusting. If the soaking time is greater than 3 hours, over-extraction causes the loss of effective components from the lees. A solid-liquid ratio < 1:8 results in insufficient solvent usage, incomplete wetting of the lees, uneven impurity removal, and poor localized modification. A solid-liquid ratio > 1:12 leads to excessive solvent waste and increased energy consumption during subsequent drying.

[0043] Furthermore, the alcohol solution includes at least one of ethanol solution, isopropanol, and methanol.

[0044] Alcoholic solutions exhibit excellent selective solubility for lipids, waxes, and soluble small-molecule impurities, removing only harmful impurities without excessively damaging the cellulose and hemicellulose skeletal structure in the distiller's grains. Ethanol is highly volatile, resulting in low energy consumption in subsequent drying steps and no solvent residue contaminating the finished paper. In contrast, non-alcoholic solvents such as water and acetone are used. Water cannot dissolve lipids and waxes, completely failing to achieve degreasing and impurity removal. Residual hydrophobic impurities form a dense barrier on the surface of the distiller's grains, completely hindering subsequent enzymatic hydrolysis and cationization reactions. Acetone's excessive degreasing ability simultaneously extracts cellulose and hemicellulose components from the distiller's grains, damaging the cellulose skeletal structure and leading to a decrease in the strength of the modified distiller's grains.

[0045] Furthermore, the volume concentration of the ethanol solution is 70%~80%.

[0046] The volume concentration of the ethanol solution is controlled at 70%~80%, for example, it can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 80%, or a combination of both. The polarity is highly matched to the polarity of lipids and waxes in the lees, allowing for rapid penetration into the intercellular spaces of the lees cell walls and efficient dissolution of lipids, waxes, and fat-soluble pigments. It dissolves only harmful hydrophobic impurities without over-extracting beneficial skeletal components such as cellulose, hemicellulose, and polysaccharides from the lees, thus preserving the fiber structure and strength of the lees. If the volume concentration is <70%, the solvent polarity is too high, significantly reducing the solubility of lipids and waxes, resulting in insufficient degreasing within the same time frame. Residual hydrophobic lipids will still form a dense coating layer on the lees surface, hindering the penetration of cellulase and cationizing agents, leading to reduced subsequent enzymatic hydrolysis efficiency. If the volume concentration is >80%, the solvent polarity is too low, significantly reducing the solubility of water-soluble small molecule impurities. These impurities will remain on the lees surface, interfering with subsequent inter-fiber hydrogen bonding, leading to a decrease in paper tensile strength.

[0047] Furthermore, in the pulp preparation step, the plant fiber pulp includes bleached softwood pulp and hardwood pulp, with a weight ratio of softwood pulp to hardwood pulp of 1:(0.5~2).

[0048] Bleached softwood pulp fibers are 2-3 mm long, with thick cell walls and high strength, providing basic tensile strength, bursting strength, and folding endurance for paper. This supports the uniform dispersion and firm bonding of modified distillers' grains particles within the paper sheet. Bleached hardwood pulp fibers are 0.5-1 mm long, fine and soft, primarily improving the uniformity, smoothness, and surface finish of the paper sheet. It also enhances printability, preventing printing defects and ink smudging caused by rough fibers. The weight ratio of softwood pulp to hardwood pulp is 1:(0.5-2), for example, 1:0.5, 1:1:, 1:1.5, 1:2, or a combination of both. This ratio range allows the pulp fibers to form a stable three-dimensional interwoven network structure with uniformly distributed pores. This provides ample bonding sites for the modified distillers' grains particles, enabling them to be evenly embedded in the fiber gaps, preventing localized aggregation or detachment, and further enhancing the interfacial bonding between the distillers' grains and plant fibers. A softwood pulp to hardwood pulp ratio greater than 2:1 results in an excessively high proportion of long fibers, uneven fiber weaving, and the formation of fiber bundles and clumps, affecting paper appearance and printability. Simultaneously, the excessively large pores in the fiber network allow modified distillers' grains to easily detach from the pores, leading to paper dusting and fuzzing. The reduced contact area between the distillers' grains and fibers weakens interfacial bonding, resulting in excessively high stiffness, poor flexibility, and a tendency to break easily. Conversely, a softwood pulp to hardwood pulp ratio less than 1:2 results in an excessively high proportion of short fibers, insufficient fiber weaving strength, and a significant decrease in the paper's basic mechanical properties, including tensile strength. The overly dense fiber network makes it difficult for modified distillers' grains to embed within the fiber gaps, forcing them to adhere only to the paper surface, making them prone to detachment during use. This also hinders the formation of hydrogen bonds between fibers, further reducing paper strength.

[0049] Furthermore, in the pulp preparation step, the weight ratio of plant fiber pulp to modified distiller's grains and functional additives is (70~95):(2~25):(3~8).

[0050] The weight ratio of plant fiber pulp, modified distillers' grains, and functional additives should be controlled at (70~95):(2~25):(3~8). For example, the weight ratio can be 70:2:3, 80:10:5, 85:15:6, 95:25:8, etc., to achieve optimal synergy among the main skeleton, functional filler, and auxiliary control. Plant fiber pulp, as the continuous phase, provides the basic mechanical strength and structural support of the paper. Modified distillers' grains, as the dispersed phase, fill the fiber gaps and enhance interfacial bonding. Functional additives, as the control phase, optimize papermaking performance and finished product stability. The three form a stable composite system. If the proportion of plant fiber pulp is too low, the fiber skeleton will be insufficient, and a continuous and stable three-dimensional interwoven network cannot be formed, resulting in reduced tensile strength. If the amount of modified distillers' grains particles is too high, they cannot be effectively wrapped by the fiber network, and a large number of particles will be free in the fiber gaps, leading to serious problems of paper dusting and fuzzing, and a decrease in surface strength. If the proportion of plant fiber pulp is too high and the amount of modified distillers' grains added is too low, it will not be able to play its role in replacing fibers and enhancing interfacial bonding. If the proportion of modified distillers' grains is too low, the filling effect on fiber gaps will be insignificant, resulting in poor interfacial bonding and reinforcement. If the proportion of modified distillers' grains is too high, excessive filler will lead to over-dilutement of the fiber network, reducing the effective contact area between fibers, significantly decreasing hydrogen bonding strength, and lowering the tensile strength of the paper. If the proportion of functional additives is too low, insufficient additive dosage will prevent effective adsorption of modified distillers' grains particles and fine fibers, resulting in reduced retention. If the proportion of functional additives is too high, it will cause pulp charge imbalance, leading to excessive flocculation of fibers and fillers, and deterioration of paper surface uniformity.

[0051] Furthermore, the functional additives include retention aids, sizing agents, and reinforcing agents; the mass ratio of retention aids, sizing agents, and reinforcing agents is (0.5~2):(1~3):(1~3).

[0052] Retention aids, through charge neutralization and bridging, adsorb negatively charged modified distillers' grains particles and fine fibers, forming stable flocs. This significantly improves the retention rate of fillers and fine fibers, reducing raw material loss with white water. Sizing agents form a hydrophobic film on the surface of fibers and modified distillers' grains, reducing the paper's water and ink absorption, and improving its water resistance, surface strength, and printability. Simultaneously, they seal the pores on the surface of the distillers' grains, preventing excessive ink penetration during printing, which can lead to bleed-through and smudging. Reinforcing agents form hydrogen bonds with the hydroxyl groups on the surface of fibers and modified distillers' grains, further enhancing the interfacial bonding between fibers and between fibers and distillers' grains. This compensates for the strength loss caused by high filler content, improving the paper's tensile strength, bursting strength, and surface strength. The combined use of retention aids, sizing agents, and reinforcing agents can simultaneously solve the problems of low retention, decreased strength, and poor water resistance even with high levels of modified distillers' grains.

[0053] The mass ratio of retention aid, sizing agent, and reinforcing agent can be 0.5:1:1, 1:3:2, 0.5:2:2, 2:3:2, etc. If the retention aid dosage is <0.5%, the charge neutralization and bridging effects are insufficient, resulting in low retention of modified distillers' grains and significant raw material loss. If the retention aid dosage is >2%, excessive flocculation forms large flocs, severely deteriorating paper surface uniformity. Excessive retention aid also remains in the paper, reducing paper whiteness and printability. If the sizing agent dosage is <1%, the sizing effect is insufficient, resulting in poor paper water resistance. If the sizing agent dosage is >3%, excessive sizing leads to an overly smooth paper surface, reduced ink absorption, and affects inter-fiber hydrogen bonding, leading to decreased paper strength. If the reinforcing agent dosage is <1.5%, the reinforcing effect is not significant and cannot compensate for the strength loss caused by high filler content; the tensile strength of the paper remains below the national standard requirements. If the reinforcing agent dosage is >3%, the reinforcing effect reaches saturation, which may actually increase pulp viscosity.

[0054] Furthermore, the retention aid includes at least one of cationic starch and polyacrylamide, the sizing agent includes at least one of alkyl ketene dimer and neutral sizing agent CS-200, and the reinforcing agent includes one of sodium carboxymethyl cellulose and guar gum.

[0055] Cationic starch, with moderate charge density and good biodegradability, adsorbs negatively charged modified distillers' grains particles through charge neutralization and can also form hydrogen bonds with hydroxyl groups on the fiber surface, thus providing a certain reinforcing effect. Polyacrylamide (PAM) connects fine fibers, ultrafine distillers' grains particles, and long fibers into large flocs through bridging, significantly improving the retention rate of fine molecules. Alkyl ketene dimer (AKD) can form a uniform hydrophobic film on the surface of fibers and distillers' grains, effectively reducing the water absorption of paper. Neutral sizing agent CS-200 has a fast curing speed, stable sizing degree, and strong adaptability to pulps with high filler content. Sodium carboxymethyl cellulose (CMC) can form a continuous polymer film on the surface of fibers and distillers' grains, connecting adjacent fibers and distillers' grains particles through hydrogen bonds, significantly improving the dry tensile strength and surface strength of paper. Guar gum has a very strong hydrogen bonding ability with plant fibers and modified distillers' grains, and also has a certain retention and filtration aid effect, which can further improve the retention rate of modified distillers' grains.

[0056] Furthermore, in the paper forming process, the drying method is a three-stage drying, which includes a first stage drying, a second stage drying, and a third stage drying. The temperature of the first stage drying is 80~90℃ and the time is 20~30s. The temperature of the second stage drying is 110~120℃ and the time is 15~20s. The temperature of the third stage drying is 90~100℃ and the time is 10~15s.

[0057] The first stage of drying gently evaporates surface water, preventing surface fiber crusting caused by rapid high-temperature drying. It also avoids premature decomposition and failure of the quaternary ammonium salt groups on the modified distillers' grains surface due to high temperatures, maintaining their electrostatic adsorption capacity with the fibers. This allows the fibers and distillers' grains to shrink slowly, initially forming a stable interfacial bond. If the temperature is below 80℃, the surface moisture evaporation rate is too slow, and pre-drying cannot be completed within 20-30 seconds. Upon entering the second stage at high temperature, the internal moisture rapidly vaporizes, causing large-scale blistering and delamination of the paper. If the temperature is above 90℃, the surface fibers rapidly dehydrate and crust, sealing the internal moisture diffusion channels and creating a dry exterior and wet interior structure, ultimately leading to uneven paper moisture content. If the time is less than 20 seconds, pre-drying is insufficient, leaving a large amount of free water on the paper surface. Entering the second stage easily generates steam bubbles, damaging the fiber network structure. If the time is greater than 30 seconds, drying is excessive, resulting in an overly dry paper surface.

[0058] The second stage of drying rapidly evaporates the bound water inside the paper. This temperature range coincides with the optimal curing temperature of the AKD / CS-200 sizing agent, promoting the film-forming reaction of the reinforcing agent and strengthening the hydrogen bonding between fibers and between fibers and distillers' grains, thus maximizing the mechanical properties of the paper. Simultaneously, this temperature is below the thermal decomposition temperature of cellulose in distillers' grains, preventing carbonization and discoloration. Temperatures below 110℃ result in insufficient curing of the sizing agent and inadequate curing rate; temperatures above 120℃ cause thermal decomposition of hemicellulose and lignin in the modified distillers' grains, and the quaternary ammonium salt cationic groups decompose and become ineffective, reducing the bonding force between the distillers' grains and fibers and exacerbating the paper dusting problem; drying times below 15s result in insufficient drying and excessive residual moisture in the paper; drying times above 20s lead to over-drying and paper breakage.

[0059] The third stage of drying slowly evaporates residual moisture, precisely controlling the final moisture content of the paper at 6%~8%. Gradual cooling eliminates internal thermal stress in the paper, avoiding warping and curling caused by rapid cooling. Temperatures below 90℃ cannot control the moisture content of the paper within the standard range, while temperatures above 100℃ result in excessively low moisture content and increased paper brittleness. A drying time of less than 10 seconds leads to uneven moisture distribution, while a drying time of more than 15 seconds results in excessive drying and a decrease in paper strength.

[0060] If a single temperature drying method is used, neither high nor low temperature can simultaneously meet the requirements of sizing curing, interface bonding, uniform moisture content, and no discoloration or deformation: high temperature drying will cause discoloration of the lees, sizing failure, and blistering of the paper; low temperature drying will result in low drying efficiency and insufficient sizing curing.

[0061] Furthermore, in the paper forming step, the calendering temperature is 60~70℃, the pressure is 0.2~0.3MPa, and the linear speed is 30~40m / min.

[0062] The calendering temperature should be controlled between 60 and 70°C, for example, it can be 60°C, 62°C, 65°C, 68°C, 70°C, or any combination thereof. This temperature range allows the plant fibers and reinforcing agent film on the paper surface to undergo slight plastic deformation, automatically filling the tiny pores and uneven areas of the paper surface. This promotes secondary hydrogen bonding between the fibers and modified distillers' grains, further strengthening the interfacial adhesion and reducing dusting and linting. At temperatures below 60°C, the fibers and reinforcing agent cannot undergo effective plastic deformation, the paper pores cannot be filled, the interfacial hydrogen bonding is weak, and the dusting problem is not significantly improved. At temperatures above 70°C, the sizing agent begins to soften and migrate, leading to uneven sizing on the paper surface, and the lignin in the distillers' grains changes color due to heat.

[0063] A pressure of 0.2~0.3 MPa, for example, can be 0.2 MPa, 0.25 MPa, 0.3 MPa, or any combination thereof. This pressure firmly compacts the loosely distributed modified distillers' grains particles and embeds them into the gaps in the fiber network, preventing the particles from falling off during printing or use. A pressure <0.2 MPa fails to compact the surface of the modified distillers' grains particles, leaving them in a loose, adhered state. A pressure >0.3 MPa excessively compresses the fiber network, resulting in excessively high paper density.

[0064] The linear speed should be 30-40 m / min, for example, it can be 30 m / min, 32 m / min, 35 m / min, 38 m / min, 40 m / min, or any combination of both. Ensure the paper has sufficient residence time between the calendering rollers to allow the temperature and pressure to fully exert their effects and achieve uniform calendering across the entire width. If the linear speed is <30 m / min, the paper will remain between the rollers for too long, resulting in over-compaction, thinning, and decreased stiffness. If the linear speed is >40 m / min, the residence time will be too short, the temperature and pressure will not be sufficient, the calendering effect will be uneven, the particles will not be compacted enough, and the problem of dust shedding cannot be effectively solved.

[0065] Furthermore, this application also provides a cultural paper prepared by the above-mentioned method, wherein the cultural paper uses the plant fiber as the matrix and modified distiller's grains as the reinforcing component, and forms chemical connections through hydrogen bonding, electrostatic adsorption and ionic bonding, while forming physical interweaving through micro-nano pore embedding and network skeleton filling, thus constituting a chemically bonded-physically interwoven composite structure.

[0066] Through the synergistic effect of chemical bonding and physical interweaving, deep integration of modified distiller's grains and plant fibers is achieved, solving the problems of weak interfacial bonding, easy particle detachment, and significant strength loss under high filler content. Chemical bonding ensures the strength of interfacial bonding, while physical interweaving provides structural stability. The synergistic effect of both increases tensile strength and surface strength while reducing powder loss even with high distiller's grains content.

[0067] Example 1 A method for preparing cultural paper includes the following steps: Step 1: Modification of distiller's grains.

[0068] Step 1.1, Pretreatment of distiller's grains: Dry the distiller's grains of sauce-flavored baijiu (moisture content 12%) with hot air at 60℃ to a moisture content of 7%, then pulverize them at high speed and pass them through a 200-mesh sieve, collecting the sieve material; add 75% ethanol aqueous solution at a solid-liquid ratio of 1:10, stir at 65℃ for 2.5h, centrifuge, wash with deionized water until pH=7.0, and dry at 50℃ to a moisture content of 4%.

[0069] Step 1.2, Enzymatic hydrolysis modification: Prepare a 12% (w / w) distillers' grains slurry, adjust the pH to 5.0, add 1.2% (w / w) of a compound enzyme solution relative to the dry weight of the distillers' grains, with a cellulase to hemicellulase mass ratio of 3:1, hydrolyze at 52℃ for 3.5 h, inactivate at 92℃ for 20 min, centrifuge and dry. The cellulase activity should be ≥10000 U / g and the hemicellulase activity should be ≥5000 U / g.

[0070] Step 1.3, Cationic Surface Activation: Add 2.5% (w / w) of 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution at a solid-liquid ratio of 1:12, adjust the pH to 10.5, stir at 62℃ for 2.5 h, wash until neutral, and then dry to a moisture content of 4% to obtain modified distiller's grains. The solid phase is the dry basis of distiller's grains, and the solid-liquid ratio is the ratio of the mass of the dry basis of the solid phase to the mass of the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution.

[0071] Take modified distiller's grains samples and use the KBr pelleting method at 4000~500 cm⁻¹ -1 The wavenumber range was scanned to analyze functional group changes, and the results are as follows: Figure 1 As shown, the infrared spectrum of the distiller's grains showed new characteristic absorption peaks, corresponding to quaternary ammonium salt cationic groups, proving that the distiller's grains modification was successful and providing a chemical basis for electrostatic bonding with fibers.

[0072] Step 2, pulp preparation.

[0073] Bleached softwood pulp and hardwood pulp were added to a hydrapulper, with the softwood pulp accounting for 50% by mass and the hardwood pulp for 30% by mass. Deionized water was added for pulping to achieve a pulp concentration of 3% in the pulper. Pulping was carried out for 25 minutes, and then the pulp was sent to a refiner for refining to a freeness of 40°SR, yielding plant fiber pulp. The plant fiber pulp was diluted to a concentration of 1.0% by mass, and 15% by mass of modified distiller's grains was added. The pulp was stirred and dispersed at 1800 rpm for 25 minutes. Then, 1% by mass of cationic starch was added and stirred for 12 minutes, followed by 2% by mass of alkyl ketene dimer (AKD) sizing agent and stirred for 15 minutes, and finally 2% by mass of CMC reinforcing agent and stirred for 10 minutes, yielding composite pulp.

[0074] Step 3: Papermaking and forming.

[0075] Step 3.1, Forming: The composite pulp is fed into the wire section of the paper machine and dewatered for 18 seconds under a vacuum of 0.04 MPa; then fed into the press section and pressed for 8 seconds under a pressure of 0.4 MPa; the moisture content of the wet paper is controlled at 45%.

[0076] Step 3.2, Drying and Shaping: A three-stage drying process is adopted: the first stage drying temperature is 85℃ and the drying time is 25s; the second stage drying temperature is 115℃ and the drying time is 18s; the third stage drying temperature is 95℃ and the drying time is 12s; dry until the paper moisture content is 7%.

[0077] Step 3.3, Post-processing: Calendering at 65℃ and 0.25MPa; calendering line speed 35m / min, to obtain cultural paper. A sample of the cultural paper was taken, treated with gold sputtering, and the fiber network and dispersion state of the modified distiller's grains were observed at 183x magnification. The results are as follows. Figure 2 As shown, the modified distillers' grains were evenly dispersed in the pulp without obvious agglomeration, and the fiber network structure was complete and dense, which directly verified the composite reinforcement mechanism of physical interweaving and chemical combination.

[0078] Example 2 A method for preparing cultural paper includes the following steps: Step 1: Modification of distiller's grains.

[0079] Step 1.1, Pretreatment of distiller's grains: Dry the distiller's grains of sauce-flavored baijiu (moisture content 12%) with hot air at 60℃ to a moisture content of 6%, then pulverize them at high speed and pass them through a 200-mesh sieve, and collect the sieve material; add 70% ethanol aqueous solution at a solid-liquid ratio of 1:10, stir at 70℃ for 3 hours, centrifuge, wash with deionized water until pH=7.2, and dry at 50℃ to a moisture content of 5%.

[0080] Step 1.2, Enzymatic hydrolysis modification: Prepare a 15% (w / w) distillers' grains slurry, adjust the pH to 5.2, add 1.5% (w / w) of a compound enzyme solution relative to the dry weight of the distillers' grains, with a cellulase to hemicellulase mass ratio of 3:1, hydrolyze at 55℃ for 4 hours, inactivate at 95℃ for 15 minutes, centrifuge and dry. The cellulase activity should be ≥10000 U / g and the hemicellulase activity should be ≥5000 U / g.

[0081] Step 1.3, cationic surface activation: Add 3% (w / w) of 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution at a solid-liquid ratio of 1:15, adjust the pH to 11, stir at 62℃ for 3 hours, wash until neutral, and then dry to a moisture content of 5% to obtain modified distiller's grains.

[0082] Step 2, pulp preparation.

[0083] Bleached softwood pulp and hardwood pulp were mixed, with the softwood pulp accounting for 40% by mass and the hardwood pulp accounting for 30% by mass. The mixture was added to a hydrapulper, where the pulp concentration was 4% by mass. Pulping was carried out for 30 minutes, followed by refining to a freeness of 45°SR, yielding plant fiber pulp. The plant fiber pulp was diluted to a concentration of 1.2% by mass, and 25% by mass of modified distiller's grains was added. The mixture was stirred and dispersed at 2000 rpm for 30 minutes. Then, 0.8% by mass of polyacrylamide retention aid was added and stirred for 12 minutes, 2.2% by mass of neutral sizing agent CS-200 was added and stirred for 15 minutes, and 2% by mass of guar gum reinforcing agent was added and stirred for 10 minutes, resulting in composite pulp.

[0084] Step 3: Papermaking and forming.

[0085] Step 3.1, Forming: The composite pulp is fed into the wire section of the paper machine and dewatered for 20 seconds under a vacuum of 0.05 MPa; then fed into the press section and pressed for 10 seconds under a pressure of 0.5 MPa; the moisture content of the wet paper is controlled at 45%.

[0086] Step 3.2, Drying and Shaping: A three-stage drying process is adopted: the first stage drying temperature is 90℃ and the drying time is 30s; the second stage drying temperature is 120℃ and the drying time is 20s; the third stage drying temperature is 100℃ and the drying time is 15s; dry until the paper moisture content is 8%.

[0087] Step 3.3, Post-processing: Calender at 70℃ and 0.3MPa; calendering line speed 40m / min, to obtain cultural paper.

[0088] Example 3 A method for preparing cultural paper includes the following steps: Step 1: Modification of distiller's grains.

[0089] Step 1.1, Pretreatment of distiller's grains: Dry the distiller's grains of sauce-flavored baijiu (moisture content 12%) with hot air at 62℃ to a moisture content of 6%, then pulverize them at high speed and pass them through a 200-mesh sieve, collecting the sieve material; add 75% ethanol aqueous solution at a solid-liquid ratio of 1:10, stir at 65℃ for 2.5h, centrifuge, wash with deionized water until pH=5.0, and dry at 50℃ to a moisture content of 4%.

[0090] Step 1.2, Enzymatic hydrolysis modification: Prepare a 12% (w / w) distillers' grains slurry, adjust the pH to 5.0, add 1.2% (w / w) of a compound enzyme solution relative to the dry weight of the distillers' grains, with a cellulase to hemicellulase mass ratio of 3:1, hydrolyze at 52℃ for 3.5 h, inactivate at 92℃ for 20 min, centrifuge and dry. The cellulase activity should be ≥10000 U / g and the hemicellulase activity should be ≥5000 U / g.

[0091] Step 1.3, cationic surface activation: Add 2.5% (w / w) of 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution at a solid-liquid ratio of 1:12, adjust the pH to 10.5, stir at 62℃ for 2.5 h, wash until neutral, and then dry to a moisture content of 4% to obtain modified distiller's grains.

[0092] Step 2, pulp preparation.

[0093] Bleached softwood pulp and hardwood pulp were mixed, with the softwood pulp accounting for 50% and the hardwood pulp for 40% by mass. The mixture was added to a hydrator pulper, where the pulp concentration was 3% by mass. Pulping was carried out for 25 minutes, followed by refining to a freeness of 40°SR, yielding plant fiber pulp. The plant fiber pulp was diluted to a concentration of 0.9% by mass, and 7% by mass of modified distiller's grains was added. The mixture was stirred and dispersed at 1800 rpm for 30 minutes. Then, 0.5% by mass of cationic starch was added and stirred for 12 minutes, followed by 1.5% by mass of AKD sizing agent and stirred for 15 minutes, and finally 1% by mass of CMC reinforcing agent and stirred for 10 minutes, resulting in composite pulp.

[0094] Step 3: Papermaking and forming.

[0095] Step 3.1, Forming: The composite pulp is fed into the wire section of the paper machine and dewatered for 17 seconds under a vacuum of 0.04 MPa; then fed into the press section and pressed for 9 seconds under a pressure of 0.4 MPa; the moisture content of the wet paper is controlled at 43%.

[0096] Step 3.2, Drying and Shaping: A three-stage drying process is adopted: the first stage drying temperature is 85℃ and the drying time is 25s; the second stage drying temperature is 115℃ and the drying time is 18s; the third stage drying temperature is 95℃ and the drying time is 12s; dry until the paper moisture content is 7%.

[0097] Step 3.3, Post-processing: Calender at 65℃ and 0.25MPa; calendering line speed 40m / min, to obtain cultural paper.

[0098] Comparative Example 1 A method for preparing cultural paper, based on Example 1, differs in that, without modification by distillers' grains, in the pulp preparation step, the plant fiber pulp is directly diluted to a mass concentration of 0.9%, and then 0.5% cationic starch is added and stirred for 12 min, 1.5% AKD sizing agent is added and stirred for 15 min, and 1% CMC reinforcing agent is added and stirred for 10 min to obtain composite pulp; other operations and conditions are the same as in Example 1.

[0099] Comparative Example 2 A method for preparing cultural paper, based on Example 1, differs in that, in step 1, the lees of Maotai-flavor liquor are dried with hot air at 60°C to a moisture content of 7%, pulverized at high speed, and passed through a 200-mesh sieve, without alcohol solution degreasing and impurity removal, enzymatic modification, or cationic surface activation treatment; in step 2, 15% by mass of the above-mentioned unmodified lees are used to replace the modified lees in Example 1; other operations and conditions are the same as in Example 1.

[0100] Comparative Example 3 A method for preparing cultural paper, based on Example 1, differs in that cationic surface activation is not performed; instead, the enzymatically modified distiller's grains are directly inactivated, washed, and dried before proceeding to the pulp preparation step in step 2; other operations and conditions are the same as in Example 1.

[0101] Comparative Example 4 A method for preparing cultural paper, based on Example 1, differs in that enzymatic modification is not performed, and the pretreated lees are directly subjected to a cationic surface activation step; other operations and conditions are the same as in Example 1.

[0102] Comparative Example 5 A method for preparing cultural paper, based on Example 1, differs in that the mass ratio of cellulase to hemicellulase in the compound enzyme in step 1.2 is adjusted to 1:1, while the remaining enzymatic hydrolysis conditions and subsequent cationic surface activation, pulp preparation, and paper forming conditions are the same as in Example 1.

[0103] Comparative Example 6 A method for preparing cultural paper, based on Example 1, differs in that, in step 1.3, a 2.5% by mass silane coupling agent KH-550 ethanol / water mixed solution is used instead of the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, and the mixture is stirred at 62°C for 2.5 h, washed until neutral, and dried; other operations and conditions are the same as in Example 1.

[0104] Performance Testing and Results Analysis The present invention tests the key performance indicators of the cultural paper prepared in the embodiments and comparative examples. The specific testing methods and results are as follows: 1. Tensile strength: Tested according to the standard method of GB / T 12914-2018 "Determination of tensile strength of paper and paperboard", and the results are expressed in the form of tensile strength.

[0105] 2. Ink absorption value: Tested according to the standard method of GB / T 12911-1991 "Determination of ink absorbency of paper and paperboard", and expressed as the percentage of ink absorbed by the paper.

[0106] 3. Printability: Using standard offset printing ink, simulated printing is performed under the same printing pressure and speed conditions. The clarity of the image and text, as well as the absence of smudging and powdering, are visually evaluated.

[0107] The results are shown in Table 1: Table 1 Performance test results of the examples and comparative examples

[0108] As shown in Table 1, the tensile strength of the cultural paper obtained in Examples 1-3 is 3.03 × 10⁻⁶. 6 ~3.32×10 6 The tensile strength of the paper was higher than that of Comparative Examples 1–6, with a tensile strength of 2.98 × 10⁻⁶ mN / m. Comparative Example 1, without the addition of modified distillers' grains, used only plant fiber pulp and functional additives to prepare cultural paper, and its tensile strength was 2.98 × 10⁻⁶ mN / m. 6 mN / m, lower than 3.15 × 10 in Example 1. 6 mN / m. This indicates that in Example 1, the addition of modified distillers' grains treated with compound enzymatic hydrolysis and cationic surface activation allows the modified grains to form hydrogen bonds, electrostatic adsorption, and physical intercalation with plant fibers. While replacing some plant fibers, it still improves paper-sheet bonding strength and maintains good printability. In Comparative Example 2, the addition of 25% unmodified distillers' grains directly reduced the tensile strength to 2.36 × 10⁻⁶ mN / m. 6 The ink absorption value increased to 64%, indicating that the dispersibility and interfacial bonding of the undegreased, unimpurified, unenzymatically modified, and uncationically activated lees were insufficient, easily leading to increased paper porosity, dusting, and printing smudging. Comparative Example 3 underwent only degreasing, unimpurification, and enzymatic modification, while Comparative Example 4 underwent only cationically activated; their tensile strengths were 2.78 × 10⁻⁶ mN / m, respectively. 6 mN / m and 2.70×10 6 The mN / m values ​​were all lower than those in Example 1, indicating that single modification is insufficient to simultaneously achieve the loosening of the lees structure, exposure of active hydroxyl groups, and introduction of cationic sites.

[0109] In Comparative Example 5, after adjusting the mass ratio of cellulase to hemicellulase to 1:1, the tensile strength was lower than that of Example 1, indicating that when the composite enzyme ratio deviates from the preferred range, the synergistic loosening of the crystalline and amorphous regions of cellulose is insufficient. In Comparative Example 6, after replacing the cationic reagent with a silane coupling agent, the tensile strength and printability were both weaker than those of Example 1, indicating that although the silane coupling agent can improve surface compatibility to a certain extent, it is difficult to stably introduce sufficient quaternary ammonium salt cation sites onto the surface of the distiller's grains, and thus cannot form strong electrostatic adsorption and ionic bonding with plant fibers. Therefore, this application, through the synergistic modification of "cellulase-hemicellulase composite enzymatic hydrolysis + cationic surface activation," can significantly improve the mechanical strength and printing stability of paper while maintaining the ink absorbance value within a suitable range.

[0110] Furthermore, the ink absorption values ​​of all embodiments were within the acceptable range of 42% to 53%, and the printability was good, indicating that the addition of modified distillers' grains would not adversely affect the key printing performance of cultural paper and would meet the requirements for actual use.

[0111] It is understood that the present invention has been described through some embodiments, and those skilled in the art will recognize that various changes or equivalent substitutions can be made to these features and embodiments without departing from the spirit and scope of the invention. Furthermore, under the teachings of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the protection scope of the present invention.

Claims

1. A method for preparing cultural paper, characterized in that, Includes the following steps: Distiller's grains modification: The distiller's grains are pretreated, then enzymatically modified using a compound enzyme, followed by cationic surface activation to obtain modified distiller's grains; wherein, the compound enzyme comprises cellulase and hemicellulase in a mass ratio of 2-4:1, the amount of the compound enzyme is 0.8%-1.5% of the dry weight of the distiller's grains, the pH range of the enzymatic modification is 4.8-5.2, the temperature is 50-55℃, and the time is 3-4h; Pulp preparation: Plant fiber pulp is mixed with the modified distiller's grains, and functional additives are added to obtain composite pulp; Papermaking process: The composite pulp is sequentially processed through papermaking, drying, and calendering to obtain cultural paper.

2. The method for preparing cultural paper as described in claim 1, characterized in that, The enzymatic modification is carried out in a distiller's grains slurry with a mass concentration of 10% to 15%. After the enzymatic modification is completed, the enzymatic product is heated to 90 to 95°C for 15 to 20 minutes to inactivate it. After centrifugation or washing, it is dried and then the cationic surface activation is carried out.

3. The method for preparing cultural paper as described in claim 1, characterized in that, The cationic surface activation is performed using a cationic reagent, which includes at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, glycidyltrimethylammonium chloride, glycidyltrimethylammonium bromide, and 3-chloro-2-hydroxypropyltrimethylammonium bromide; the cationic surface activation temperature is 60℃~65℃, and the time is 2h~3h. Preferably, the mass fraction of the cationizing agent is 2% to 3%, and the solid-liquid ratio of the cationizing agent to the distiller's grains is 1:(10 to 15).

4. The method for preparing cultural paper as described in claim 1, characterized in that, The method for pretreatment of distiller's grains includes: Drying and pulverizing: The lees are dried to a moisture content of ≤8%, and then pulverized and sieved in sequence to obtain lees particles that can pass through a 200-mesh standard sieve; Degreasing and impurity removal: The lees particles are soaked in an alcohol solution, then washed and dried. The soaking temperature of the alcohol solution is 60~70℃, the soaking time of the alcohol solution is 2~3h, and the solid-liquid ratio of the lees particles to the aqueous alcohol solution is 1:(8~12). Preferably, the alcohol solution includes at least one of ethanol solution, isopropanol, and methanol; Preferably, the volume concentration of the ethanol solution is 70% to 80%.

5. The method for preparing cultural paper as described in claim 1, characterized in that, In the pulp preparation step, the plant fiber pulp includes bleached softwood pulp and hardwood pulp, and the weight ratio of the softwood pulp to the hardwood pulp is 1:(0.5~2).

6. The method for preparing cultural paper as described in claim 1, characterized in that, In the pulp preparation step, the weight ratio of the plant fiber pulp to the modified distiller's grains and the functional additives is (70~95):(2~25):(3~8).

7. The method for preparing cultural paper as described in claim 1, characterized in that, The functional additives include retention aids, sizing agents, and reinforcing agents; the mass ratio of the retention aid, sizing agent, and reinforcing agent is (0.5~2):(1~3):(1~3). Preferably, the retention aid includes at least one of cationic starch and polyacrylamide, the sizing agent includes at least one of alkyl ketene dimer and neutral sizing agent CS-200, and the reinforcing agent includes one of sodium carboxymethyl cellulose and guar gum.

8. The method for preparing cultural paper as described in claim 1, characterized in that, In the papermaking process, the drying method is a three-stage drying, which includes a first stage drying, a second stage drying, and a third stage drying. The temperature of the first stage drying is 80~90℃ and the time is 20~30s. The temperature of the second stage drying is 110~120℃ and the time is 15~20s. The temperature of the third stage drying is 90~100℃ and the time is 10~15s.

9. The method for preparing cultural paper as described in claim 1, characterized in that, In the papermaking process, the calendering temperature is 60-70℃, the pressure is 0.2-0.3MPa, and the linear speed is 30-40m / min.

10. A type of cultural paper prepared by the method of any one of claims 1-9, characterized in that, The cultural paper uses the plant fiber as the matrix and the modified distiller's grains as the reinforcing component. It forms chemical connections through hydrogen bonding, electrostatic adsorption and ionic bonding, and forms physical interweaving through micro-nano pore embedding and network skeleton filling, thus forming a chemically bonded-physically interwoven composite structure.